Recombinant LH supplementation to recombinant FSH during induced ovarian stimulation in the GnRH-antagonist protocol: A meta-analysis - Baruffi, Ricardo L.R.; Mauri, A. L. [UNESP]; Petersen, C. G. [UNESP]; Felipe, V.; Martins, A. M C; Cornicelli, J.; Cavagna, M.; Oliveira, J. B A; Franco, J. G. (Elsevier, 2007)
This study aims to compare the efficacy of recombinant LH (rLH) supplementation for ovarian stimulation in gonadotrophin-releasing hormone-antagonist protocol for IVF/intracytoplasmic sperm injection cycles. Search strategies included online surveys of databases. The fixed effects model was used for odds ratio (OR) and effect size (weighted mean difference, WMD). Five trials fulfilled the inclusion criteria. When the meta-analysis was carried out, advantages were observed for the LH supplementation protocol with respect to higher serum oestradiol concentrations on the day of human chorionic gonadotrophin administration (P < 0.0001; WMD: 514, 95% CI 368, 660) and higher number of mature oocytes (P = 0.0098; WMD: 0.88, 95% CI 0.21, 1.54). However, these differences were not observed in the total amount of recombinant FSH (rFSH) administered, days of stimulation, number of oocytes retrieved, the clinical pregnancy rate per oocyte retrieval, the implantation rate and miscarriage rate. This result demonstrates that the association of rLH with rFSH may prevent any decrease in oestradiol after antagonist administration and that a significantly higher number of mature oocytes was available for laboratory work. Nevertheless, it failed to show any statistically significant difference in clinically significant end-points in IVF (implantation and pregnancy rates). Additional randomized controlled trials are needed to confirm these results further. © 2007 Published by Reproductive Healthcare Ltd.
Keywords: GnRH antagonist; Ovarian stimulation; Recombinant FSH; Recombinant LH; cetrorelix; chorionic gonadotropin; estradiol; gonadorelin antagonist; recombinant follitropin; recombinant luteinizing hormone; cell count; clinical protocol; clinical trial; combination chemotherapy; controlled clinical trial; controlled study; data base; drug dose increase; drug dose reduction; drug efficacy; drug withdrawal; effect size; estradiol blood level; evidence based medicine; fertilization in vitro; hormonal regulation; human; intracytoplasmic sperm injection; low drug dose; meta analysis; monotherapy; multiple cycle treatment; oocyte maturation; ovulation induction; pregnancy rate; randomized controlled trial; risk assessment; single drug dose; spontaneous abortion; systematic review; Estradiol; Female; Fertilization in Vitro; Follicle Stimulating Hormone; Gonadotropin-Releasing Hormone; Humans; Luteinizing Hormone; Ovulation Induction; Pregnancy; Pregnancy Rate; Randomized Controlled Trials; Recombinant Proteins; Sperm Injections, Intracytoplasmic; Treatment Outcome